Evaluation of Water Retention Capacity of Bulkheads in Underground Coal Mines. (13th January 2021) - Hang, Yuan; Jin, Lichuang; Yang, Binbin; Li, Ning; Yuan, Shichong; Gao, Zhilin; Sun, Linxuan; Zheng, Sen; Hu, Mingming
Abstract : The mechanism of water flow in and around the bulkheads and the surrounding rock is studied for Panel No. 21102 in the Sanhejian coal mine in Xuzhou, China. Based on an analysis of the properties of the bulkheads and the surrounding rock, three types of water conducting pathways are identified: (1) a water conducting pathway at the interface between the bulkhead and the surrounding rock; (2) a water conducting pathway in the faults of the rock; and (3) a water conducting pathway in the fractures of the rock. The possibility of these three pathways for water flow at Panel No. 21102 is analyzed, and the connectivity coefficient of the water conducting pathway is determined. The expression for calculating the critical hydraulic gradient of the rock by using the connectivity coefficient in the water conducting pathways is presented which is based on the permeability and integrity of the rock. The ratios of the critical hydraulic gradient to the steady state hydraulic gradient are calculated for 13 mines in China. An acceptable safety factor in controlling the water flow for the bulkhead is found to be 1.68. When the safety factor is less than 1.68, water leakage has occurred in a number of cases. Finally, changes in the water pressure in the bulkheads with time and changes in the seepage flow with time in the surrounding rock are analyzed. It is found that there is a good correlation between the rate of water flow and water pressure which confirms that water pressure plays a decisive role in controlling seepage from the rock in and around the bulkheads.